Bub : Essays from Just North of Nashville - Bratcher, Drew, 1983- (Book collections on Project MUSE., 2022)
"In his debut collection, Nashville native and Iowa MFA Drew Bratcher writes musically about memory and memorably about music in uncommonly beautiful essays that announce the arrival of a major new voice. The title essay, a requiem in fragments, tells the story of a grandfather through his ear, comb, hands, El Camino, and clothes. With a descriptive precision redolent of John Berger and the literary portraiture of Annie Ernaux, Bratcher delivers a tough and moving tribute to a man who 'went on ahead, on up the road, and then the road turned.' Elsewhere, Bratcher directs his attention to Johnny Cash's looming presence over his childhood ('a landmark, fixed and orienting'), the relative pain of red paper wasp stings, Dolly Parton's generative homesickness, the humiliations and consolations of becoming a new father, the experience of hearing his name in a Taylor Swift song, and the mystifying hymns treasured by both his great grandmother and D.H. Lawrence. Seamlessly blending memoir and arts criticism and aiming at both the heart and the head, this is a book about listening closely to stories and songs, about leaving home in order to find home, and about how the melodies and memories absorbed along the way become 'a living music that advances and prevails upon us at formative moments, corralling chaos into the simple, liberating stockade of verse, chorus, verse'"--